1989
DOI: 10.1073/pnas.86.23.9168
|View full text |Cite
|
Sign up to set email alerts
|

Structural dependence of the inhibition of mitochondrial respiration and of NADH oxidase by 1-methyl-4-phenylpyridinium (MPP+) analogs and their energized accumulation by mitochondria.

Abstract: Nineteen structural analogs of 1-methyl- Studies over the past 5 years in our laboratories and by others have provided substantial support for the hypothesis that the expression of the neurotoxicity of 1-methyl-4-phenyl-1,2, 3,6-tetrahydropyridine (MPTP) and the Parkinsonism it produces involves the following steps, all of which occur in the central nervous system. The initial bioactivation of M1PTP is catalyzed by monoamine oxidase (MAO), yielding 1-methyl-4-phenylpyridinium (MPP+) as the ultimate oxidation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…For example, a significant reduction in the activity of Complex I has been found postmortem in the substantia nigra, platelets, and skeletal muscle of patients with IPD (Haas et al, 1995;Mizuno et al, 1998;Parker et al, 1989;Schapira et al, 1990). Animal studies using model compounds such as 1-methyl-4-phenyl-1,2,5,6-tetrahydropyridine to induce Parkinson's lesions also confirm the correlation between a defected Complex I and PD-type neuropathological damages (Burns et al, 1983;Langston et al, 1983;Nicklas et al, 1985;Ramsay et al, 1989). A recent study further demonstrates that chronic exposure to rotenone, a Complex I inhibitor, can cause highly selective nigrostriatal dopaminergic degeneration that is associated with certain PD syndromes in rats (Betarbet et al, 2000).…”
mentioning
confidence: 80%
“…For example, a significant reduction in the activity of Complex I has been found postmortem in the substantia nigra, platelets, and skeletal muscle of patients with IPD (Haas et al, 1995;Mizuno et al, 1998;Parker et al, 1989;Schapira et al, 1990). Animal studies using model compounds such as 1-methyl-4-phenyl-1,2,5,6-tetrahydropyridine to induce Parkinson's lesions also confirm the correlation between a defected Complex I and PD-type neuropathological damages (Burns et al, 1983;Langston et al, 1983;Nicklas et al, 1985;Ramsay et al, 1989). A recent study further demonstrates that chronic exposure to rotenone, a Complex I inhibitor, can cause highly selective nigrostriatal dopaminergic degeneration that is associated with certain PD syndromes in rats (Betarbet et al, 2000).…”
mentioning
confidence: 80%
“…1), then all MPP ÷ analogs which are good inhibitors of respiration in mitochondria should also be effective inhibitors of NADH oxidation in inverted membranes. With over 20 MPP ÷ analogs tested, this was true in each case [43]. Thus, 4'-methyl-MPP ÷ is much more potent than MPP ÷ in mitochondria; its IC50 value for inhibiting NADH oxidase activity in submitochondrial particles (ETP) is 10 times lower than that of MPP ÷.…”
Section: Structural Requirements For In-hibitionmentioning
confidence: 91%
“…This concentration is rapidly reached in response to the electrical gradient across the membrane, Some characteristics of the uptake initially suggested that the process might be carrier-mediated [1], but studies using charged and uncharged structural analogs indicated passive Nernstian transport, as for other lipophilic cations [42]. Interpretation of the process was further complicated by the fact that various MPP ÷ analogs accumulated to very different levels in the mitochondrion, depending on their structures [43]. The confusion was resolved by the demonstration that the lipophilic anion, tetraphenylboron (TPB-), which carries cations into hydrophobic environments by ion-pairing, dramatically enhances the inhibition of mitochondrial respiration by MPP + [44][45][46].…”
Section: From Accumulation In Mitochondria To Cell Deathmentioning
confidence: 99%
See 2 more Smart Citations